2016
DOI: 10.2174/1567205013666160129095138
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomic-Driven Elucidation of Serum Disturbances Associated with Alzheimer';s Disease and Mild Cognitive Impairment

Abstract: Numerous efforts have been made in the last years to discover potential biomarkers of Alzheimer's disease and its progression from mild cognitive impairment, considered as an intermediate phase in the development of Alzheimer's disease from normal aging. However, there is still a considerable lack of understanding about pathological mechanisms underlying to disease. In the present study, serum metabolomics based on ultra-high-performance liquid chromatographymass spectrometry was applied to investigate metabol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
27
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 41 publications
(32 citation statements)
references
References 52 publications
4
27
1
Order By: Relevance
“…The affected pathways range from fatty acid metabolism, one-carbon metabolism, energy metabolism, Krebs cycle, mitochondrial function, nucleic acid metabolism, but also neurotransmitter and amino acid metabolism, and lipid biosynthesis [165] , [166] . In line with these findings, patients with AD also show altered phospholipid metabolism [33] , [167] , [168] . As most of these metabolic pathways use nutrients, the aforementioned findings indirectly confirm the lower nutrient status observed in the current and former meta-analyses of circulatory nutrient levels.…”
Section: Discussionsupporting
confidence: 74%
“…The affected pathways range from fatty acid metabolism, one-carbon metabolism, energy metabolism, Krebs cycle, mitochondrial function, nucleic acid metabolism, but also neurotransmitter and amino acid metabolism, and lipid biosynthesis [165] , [166] . In line with these findings, patients with AD also show altered phospholipid metabolism [33] , [167] , [168] . As most of these metabolic pathways use nutrients, the aforementioned findings indirectly confirm the lower nutrient status observed in the current and former meta-analyses of circulatory nutrient levels.…”
Section: Discussionsupporting
confidence: 74%
“…These studies revealed significant disturbances in the homeostasis of various lipid classes (e.g., phospholipids, fatty acids, glycerolipids), energy-related metabolites, neurotransmitters, and other metabolites, thus evidencing the utility of simple and easily available serum samples in clinical research. Furthermore, these findings were then validated using orthogonal hyphenated approaches, such as UHPLC-MS [36,37], GC-MS [37,38], and CE-MS [39], demonstrating the reliability of direct MS-based metabolomics. This DIMS platform was latterly adapted for the analysis of other biological matrices, such as urine [40], brain [41], peripheral organs (i.e., liver, kidney, thymus, spleen) [42], as well as muscle, hepatopancreas, and antennal gland [43], providing very valuable results to accomplish a preliminary metabolomic screening prior to the application of other complementary techniques.…”
Section: Application Of Dims Metabolomicmentioning
confidence: 89%
“…Alterations in serum levels of eicosanoids, amino acids and related compounds, and metabolites involved in the urea cycle demonstrated that depletion of interleukin-4 exacerbates AD pathology in this transgenic line. It should be noted that all these results obtained by DMS analysis were subsequently validated by applying various orthogonal metabolomic techniques, including LC-MS, GC-MS and CE-MS [ 45 , 46 , 47 , 48 ], thus demonstrating the potential of MS-fingerprinting approaches to carry out fast and accurate screening of complex metabolic networks.…”
Section: Application Of Direct Mass Spectrometry-based Metabolomicmentioning
confidence: 90%